Considerations of Fairness and Strategy: Experimental Data from Sequential Games - Prasnikar, V.; Roth, A. E. (Quarterly Journal of Economics, 1992)
Laboratory data from bargaining experiments have started a debate about the prospects for various parts of game theory as descriptive theories of observable behavior, and about whether, to what extent, and how a successful descriptive theory must take into account peoples' perceptions of “fairness.” Plausible explanations of the observed bargaining phenomena advanced by different investigators lead to markedly different predictions about what should be observed in three different games. A sharp experimental test is thus possible on this class of games, and the present paper reports the results of such a test.